Transforming the Pandemic into a gateway for zeroing waste-related emissions at the University of Colombo, Sri Lanka - Erandathie Lokupitiya; Sandani Siriwardhana (Journal of Sustainability Perspectives, 2022)
The University of Colombo (UoC) has turned the Covid-19 pandemic into a win-win situation by adopting new measures to overcome limitations the pandemic has brought in while improving its overall waste management. It has incorporated a paperless system by conducting academic work online, including applying for new courses, distributing e-learning material and submitting assignments. Every lecture, meeting, and function has been held virtually, eliminating food, paper, plastic and decoration waste. Students now study from home and employees have been reporting to work according to rosters, reducing food and office waste generation significantly. The employees now adhere to the pre- and newly included post-pandemic environmental guidelines, litterless lunches, and have been provided with shuttle services for safer commuting, leading to lower greenhouse gas emissions. Identifying the potential environmental damage through improper disposal, using reusable masks is being promoted through regular online awareness programmes; eco-friendly sanitizers are used instead of liquid soap, which consumes water and generates wastewater. Although the amount of waste generated during the pandemic is low, the UoC-owned Waste Storage Center continues to function with waste segregation and recycling, and the composting facility is currently expanding its production. The waste reduction has also caused lowered waste-related greenhouse gas emissions.Keyword: Waste Management, Paperless System, Guidelines, Waste Storage Center, Segregation and Recycling